2009
DOI: 10.1242/jeb.034579
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal response to feeding in seawater gulf toadfish, Opsanus beta, includes elevated base secretion and increased epithelial oxygen consumption

Abstract: SUMMARY Intestinal HCO 3-secretion is essential to marine teleost fish osmoregulation and comprises a considerable source of base efflux attributable to both serosal HCO 3 -and endogenous CO 2 hydration. The role of intestinal HCO 3 -secretion in dynamic acid-base balance regulation appears negligible in studies of unfed fish, but evidence of high intestinal fluid [HCO 3 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 43 publications
6
36
0
Order By: Relevance
“…Bucking and colleagues (Bucking et al, 2009) evaluated this idea using an in vitro gut sac technique and showed that net intestinal base secretion rates were greatly elevated after feeding in seawater-acclimated trout, as postulated. Taylor and Grosell (Taylor and Grosell, 2009) provided similar evidence in the marine toadfish using an Ussing chamber approach. However, intestinal base secretion remained low and unchanged after feeding in freshwater-acclimated trout (Bucking et al, 2009), and so the explanation for freshwater fish with acid-secreting stomachs is uncertain.…”
Section: The Absence Of a Change In Net Acid-base Fluxes After Feedingmentioning
confidence: 74%
See 3 more Smart Citations
“…Bucking and colleagues (Bucking et al, 2009) evaluated this idea using an in vitro gut sac technique and showed that net intestinal base secretion rates were greatly elevated after feeding in seawater-acclimated trout, as postulated. Taylor and Grosell (Taylor and Grosell, 2009) provided similar evidence in the marine toadfish using an Ussing chamber approach. However, intestinal base secretion remained low and unchanged after feeding in freshwater-acclimated trout (Bucking et al, 2009), and so the explanation for freshwater fish with acid-secreting stomachs is uncertain.…”
Section: The Absence Of a Change In Net Acid-base Fluxes After Feedingmentioning
confidence: 74%
“…This is not to say that rates in seawater preparations were low, as they were in the range reported for many other marine fish (Wilson et al, 2002;Wilson and Grosell, 2003;Grosell et al, 2005;Grosell et al, 2009a;Grosell, 2006;Grosell and Taylor, 2007;Bucking et al, 2009;Taylor and Grosell, 2009). Rather, freshwater rates were unexpectedly high.…”
Section: Intestinal Base Secretion In Relation To Salinity and Feedinmentioning
confidence: 81%
See 2 more Smart Citations
“…The effect of feeding on a variety of physiological parameters in teleosts has been investigated recently in seawater [e.g. acid-base regulation (Bucking et al, 2009;Taylor et al, 2007;Taylor and Grosell, 2006;Taylor and Grosell, 2009;Wood et al, 2010), salt balance (Bucking et al, 2011;Taylor et al, 2007;Taylor and Grosell, 2006)] and freshwater [e.g. acid-base regulation (Bucking and Wood, 2008;Cooper and Wilson, 2008;Taylor et al, 2007;Wood et al, 2010), salt balance (Bucking and Wood, 2006a;Bucking and Wood, 2007;Taylor et al, 2007), water balance (Bucking and Wood, 2006b)].…”
Section: Introductionmentioning
confidence: 99%